Shear strength prediction method of the UHPC keyed dry joint considering the bridging effect of steel fibers. (15th March 2022) - Hu, Yuqing; Qiu, Jiangrui; Li, Zhijie; Yao, Yiming; Liu, Jiaping; Wang, Jingquan
Highlights: A formula was proposed to better predict the shear strength of UHPC keyed dry joints. The proposed formula was calibrated using FE model. The validity of the proposed formula was verified by push-off test results. Abstract: The joints between segments of the precast ultra-high performance concrete (UHPC) segmental bridge (PUSB), which transmit compressive and shear stresses, require special attention in design. The shear strength of these joints is significantly improved in comparison with that of normal strength concrete (NSC) joints due to the excellent mechanical properties of UHPC. Nevertheless, little attention has been paid to predict the shear capacity of UHPC joints directly considering the shear contribution of steel fibers. This paper develops a new shear strength model for UHPC-keyed dry joints incorporating transferring mechanisms of three primary shear component based on previous experimental results and numerical simulation. Based on the modified compression-field theory, the shear contribution by the matrix in UHPC keys is mainly influenced by normal compressive stress and area of all bases of keys. Based on the mesoscale fiber–matrix discrete model, the shear contribution by steel fibers was affected by the steel fiber length, diameter, type, and volume fraction. To obtain more accurate prediction results, a reduction coefficient was utilized for UHPC multi-keyed dry joints in the proposed shear strength formula on grounds of regression analysis. The reliability and accuracy of these results were then verified by experimental results of 27 push-off tests available, with mean and standard deviations between the predicted and experimental shear strength of 0.98 and 0.27, respectively. Thus, the proposed formula can be used to predict the shear strength of UHPC dry joints with single and multiple shear keys.